A FOREIGN BODY OF THE URETHRA AND BLADDER (CLINICAL CASE) - Trishch, Volodymyr; Mysak, Andriy; Khorosh, Volodymyr; Trishch, Andrii (Eastern Ukrainian Medical Journal, 2025)
Introduction. The use of various foreign objects by men for insertion into the urethra, which is associated with sexual motives, is rare in emergency urology, but deserves attention in view of possible formidable complications that require an individual approach in treatment tactics. Often introduced foreign bodies migrate into the bladder. Clinical manifestations can be diverse, but usually patients hide them along with the fact of introducing a foreign body into the urethra, which complicates the diagnostic process. We would like to share our own observation from clinical practice - a patient who self-introduced a foam sealant into the urethra, which resulted in urethral obturation, "migration" of the sealant into the bladder with the secondary development of peritonitis, which became an indication for cystotomy, as a result of which more than a liter of foam sealant was removed and lower median laparotomy with drainage of the abdominal cavity were performed, as serous fluid was present. Case report. A 43-year-old patient was urgently hospitalized in the urology department of the Ternopil Regional Clinical Hospital with acute urinary retention and peritonitis. Catheterization of the urinary bladder was impossible due to an obstruction in the anterior part of the urethra. According to the obtained results of laboratory examinations, moderate changes of an inflammatory nature were noted in the general blood test. Data from additional examination methods indicated free fluid in the iliac areas and overflow of the urinary bladder with heterogeneous contents. About one liter of foam sealant was found during cystotomy and about 400 ml of turbid serous content during lower middle laparotomy. Violation of the integrity of the wall of the intestine and bladder was not detected. Removal of the foam sealant from the urethra was performed a week later, as it was impossible during the operation due to its intimate adhesion to the mucous membrane. In the postoperative period, the patient was examined by a psychiatrist, according to the results of which he was diagnosed with a mild form of mental retardation. Three weeks later, the patient was discharged from the clinic for outpatient treatment, with independent urination restored. When examining the patient after 3 and 6 months, no pathological changes in the organs of the abdominal cavity and urinary system were found. The patient is satisfied with his sex life. Discussion. The introduction of foreign objects of various structures into the urethra by men, usually with the aim of "improving" sexual function, often against the background of alcohol, drug intoxication or mental illness, can lead to such serious complications as trauma (rupture, perforation) of the urethra or bladder. Foreign objects are often introduced by men into the bladder, or these objects are independently "moved" into the bladder. In our clinical case, there was an independent introduction of a mounting foam sealant into the urethra, which, having a liquid consistency, was introduced by the patient into the bladder, with the subsequent development of peritonitis without violation of the integrity of the bladder and intestines. Usually, patients, out of fear of condemnation, hide the fact of self-introduction of foreign bodies into the urethra, which was also relevant for our case. It is also important to conduct a psychiatric examination for the presence of mental illnesses that may cause such behavior. In the postoperative period, the patient was examined by a psychiatrist, according to the results of which mild mental retardation was diagnosed. Treatment of such patients requires surgical intervention, with the removal of foreign bodies, usually endoscopically. But there is often a need for an open method of surgical removal of a foreign body and it depends on its localization, size, length of stay, structure, etc. Considering the clinic of acute urinary retention, the impossibility of passing a urethral catheter and the symptoms of peritonitis, a lower median laparotomy with drainage of the abdominal cavity was performed. cystotomy with removal of foam sealant, cystostomy for urine derivation. In this case, peritonitis was probably due to the reaction of the peritoneum to the foam sealant, since there was no violation of the integrity of the intestines and bladder. We have not observed similar cases in scientific publications. Removal of the sealant from the urethra required a surgical delaying tactics, as the latter was tightly adhered to the mucous membrane, as demonstrated in scientific publications of similar clinical cases. Conclusions. Self-insertion of foreign objects into the urethra by men can cause significant complications. In the given clinical case, the introduction of a foam sealant into the urethra with migration into the bladder caused peritonitis. Foreign objects of this structure are practically impossible to remove from the urethra and require delayed surgical tactics. Such patients require psychiatric evaluation for mental illnesses that may cause such behavior.